Adubação nitrogenada em cobertura no feijoeiro com suplementação de molibdênio via foliar - Calonego, Juliano Carlos [UNESP]; Ramos Junior, Edson Ulisses; Barbosa, Rodrigo Domingues; Pereira Leite, Glauber Henrique [UNESP]; Grassi Filho, Hélio [UNESP] (Univ Federal Ceara, Dept Geol, 2010)
The objective of this work was to evaluate the effect of leaf spray of molybdenum (Mo) and nitrogen (N) rates in common bean (Phaseolus vulgaris L.), cultivar Carioca Precoce, evaluating the yield components, yield and leaves nitrate levels. The research was carried out in Botucatu, State of São Paulo, Brazil. The sowing of the beans (06/03/2003) was made with the supply of 230 kg ha(-1) of NPK (4-30-10) granulated fertilizer at planting. The experiment was a complete randomized block, with four replications and a 5 x 2 factorial arrangement, involving five N rates (25; 50; 75 and 125 kg ha(-1)), applied 20 days after emergency (DAE), with or without 80 g ha(-1) of Mo, applied on leaves at 25 DAE. The Mo absence by leaf spray promoted the nitrate accumulation in the leaves in treatments with higher rates of N. The weight of 100 grains increased with the Mo by leaf spray, reducing the need for N to get the best results. The molybdenum fertilization increased bean yield regardless of N rate applied to the beans.
Nitrogen topdressing fertilization on common bean with leaf spray of molybdenum
Keywords: Phaseolus vulgaris (L.); Molybdenum fertilization; Nitrogen assimilation